Studies of life positioning : a new sociocultural approach to psychobiography - Martin, Jack (Professor of psychology) (New York : Routledge, 2024)
"This book illustrates how Life Positioning Analysis can be used as a theoretical and methodological approach to sociocultural psychobiography. Life positioning psychobiography studies lives as they unfold within a world of interactivity. It recognizes and portrays us as social beings embedded and developing within our life relationships and circumstances and striving to make something of our lives. Here, Jack Martin presents both single-subject and dual-subject studies of social psychologist Stanley Milgram, former Canadian Prime Minister Pierre Elliott Trudeau, existential humanist Ernest Becker, American heiress and child advocate Dorothy Burlingham and her life partner, renowned psychoanalyst Anna Freud, and indigenous athlete Jim Thorpe and his college coach Glenn "Pop" Warner. These case studies provide vividly memorable demonstrations of how we are positioned by circumstances and others, and come to position ourselves as socioculturally constituted, psychological persons. In so doing, they offer a systematic framework for studying the lives of people that shows sociocultural and social psychological development without resorting to mentalistic theories, concepts, and interpretations. The book will be of interest to students and scholars in areas related to sociocultural and developmental psychology, the psychology and sociology of personhood, theoretical psychology, qualitative methodology, and social science and life writing more generally"--
Keywords: Social psychology; Developmental psychology; Social sciences -- Philosophy; PSYCHOLOGY / Personality; PSYCHOLOGY / Research & Methodology; PSYCHOLOGY / Developmental / General